Hubungan Kejadian Hipertensi Dengan Fungsi Kognitif Lansia Di Taman Bodhi Asri Tahun 2024 - Evi Martina, Siska; Rumondang Gultom; Janno Sinaga; Icce Triwani Sitompul (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Hypertension is a condition of increased blood pressure above normal levels. Unmanaged hypertension can increase the risk of various life-threatening diseases and interfere with daily life functions including causing decreased cognitive function. This study aims to evaluate the relationship between the incidence of hypertension and cognitive function in the elderly at Taman Bodhi Asri in 2024. This type of research is descriptive correlation with a cross-sectional approach. The research location was at Taman Bodhi Asri Medan. The research time was carried out from November 2023 to June 2024. The study population was 48 elderly people aged 60-<85 years, with a sample of 48 respondents taken using the total sampling technique. The measuring instruments used were a sphygmomanometer for measuring blood pressure and a questionnaire sheet for cognitive function, the data were analyzed using the Spearman rank test. The results of the study showed a univariate analysis of the frequency distribution of the characteristics of hypertension and cognitive function in the elderly, the results showed that systolic and diastolic blood pressure in the elderly in Taman Bodhi Asri in 2024 were mostly grade 2 hypertension at 58.4%. For severe cognitive impairment as much as 41.8%. Based on the Spearman Rank Test, the sig value = 0.001 <0.005 was obtained. The conclusion of this study is that there is a relationship between systolic and diastolic blood pressure and cognitive function in the elderly in Taman Bodhi Asri in 2024. The suggestion from this study is for the elderly to be able to routinely control blood pressure, do regular exercise, regulate food consumption, and get proper rest so that cognitive dysfunction in the future can be avoided. And for the orphanage, it is hoped that it can detect cognitive dysfunction so that it can prevent the quality of life of hypertension patients from getting worse.